STYLISTIC FEATURES OF COMPLEX SYNTACTIC CONSTRUCTIONS (BASED ON UZBEK AND ENGLISH LANGUAGES) (International journal of artificial intelligence, 2024)
This article explores the stylistic characteristics of complex syntactic constructions in the English and Uzbek languages. Drawing on comparative analysis, it identifies how these constructions contribute to expressiveness, clarity, and nuance in both languages. The study examines literary texts, academic writings, and conversational examples to determine the aesthetic and functional differences. Findings reveal that while English heavily relies on subordination and concise coordination for stylistic effect, Uzbek often uses parataxis and rich conjunctive patterns to enhance rhythm and clarity. This contrast underscores the influence of linguistic structure on stylistic choices.